Neuroimaging as a Selection Tool and Endpoint in Clinical and Pre-clinical Trials - Muir, Keith W. (Transl Stroke Res, 2016)
Standard imaging in acute stroke enables the exclusion of non-stroke structural CNS lesions and cerebral haemorrhage from clinical and pre-clinical ischaemic stroke trials. In this review, the potential benefit of imaging (e.g., angiography and penumbral imaging) as a translational tool for trial recruitment and the use of imaging endpoints are discussed for both clinical and pre-clinical stroke research. The addition of advanced imaging to identify a “responder” population leads to reduced sample size for any given effect size in phase 2 trials and is a potentially cost-efficient means of testing interventions. In pre-clinical studies, technical failures (failed or incomplete vessel occlusion, cerebral haemorrhage) can be excluded early and continuous multimodal imaging of the animal from stroke onset is feasible. Pre- and post-intervention repeat scans provide real time assessment of the intervention over the first 4–6 h. Negative aspects of advanced imaging in animal studies include increased time under general anaesthesia, and, as in clinical studies, a delay in starting the intervention. In clinical phase 3 trial designs, the negative aspects of advanced imaging in patient selection include higher exclusion rates, slower recruitment, overestimated effect size and longer acquisition times. Imaging may identify biological effects with smaller sample size and at earlier time points, compared to standard clinical assessments, and can be adjusted for baseline parameters. Mechanistic insights can be obtained. Pre-clinically, multimodal imaging can non-invasively generate data on a range of parameters, allowing the animal to be recovered for subsequent behavioural testing and/or the brain taken for further molecular or histological analysis.